Teachers and clinical students' perception of the core competencies of different subjects of the undergraduate BDS curriculum (Bangladesh Journal of Medical Education, 2017)
Background: Curriculum planning and designing is not a static process, rather a continuous process done regularly through a system. More than one decade have elapsed since the Centre for Medical Education (CME), in 1988, developed a national Undergraduate Dental Curriculum which was supposed to be community-oriented and competency based. The curriculum was partially implemented with the advancement of dental health science and application of newer techniques in dental practices in developed and developing countries.Rationale: Competency is the ability to combine evidence based knowledge, personal attitudes, and clinical skills to undertake holistic dental care. Personal attributes may include creativity, ethics, aesthetics, and critical sense and personal attributes include a desire for patient wellbeing and to self-evaluate the effectiveness of the treatment. As life-long learning becomes a crucial attribute for all modern clinicians, the ability to self-assess performance and identify future learning goals is an essential skill that needs to be developed in a modern healthcare curriculum. Self-assessment, self-reflection and selfregulation can promote a deeper understanding in current knowledge. The essential professional clinical skills may include a) diagnosis and treatment planning b) Preventative measures c) patient treatment and rehabilitation. Other skills that may be essential include professionalism, administrative and promotional skills. It is important that universities and dental schools help students nurture these values from a very early stage.Objectives: The present study was undertaken to identify the teachers and clinical students' perception of the core competencies of different subjects of the undergraduate BDS curriculum.Methods: This descriptive type of cross sectional study was conducted in seven public and private dental colleges of Bangladesh after getting written permission from the principal of the respective dental colleges. Voluntary participation of the students was ensured and the names of the students' as well as teachers were kept confidential. The teachers and students of final years from the different dental colleges were the study population; among them four hundred (400) students and one hundred twenty teachers (120) were taken as sample by convenient sampling. Data collection instrument was a semistructured questionnaire with 5-point Likert scale for final year students' and in depth interview was used for teachers.Results: The study revaled that 95% mentioned that introduction part of the curriculum competency in relation to the knowledge, skills and attitude of a dental graduate must be mentioned. Nearly 97 of the students mentioned that competency acquired by the newly passed dental graduate from the BDS course was satisfactory.Conclusion: Competency-based dental education is a continuous process in maintaining a degree of quality consistent with patient well-being and effective treatment management path, which the graduating dentist should achieve. The cultural and socioeconomic diversity among different communities might have an impact on the profile of the professional needed by the society.Bangladesh Journal of Medical Education Vol.8(2) 2017: 24-28